KOMUNIKASI INTERPERSONAL ANTARA KURIR DENGAN PELANGGAN (Studi Kasus Jasa Pengiriman Cash On Delivery (COD) Shoope Express Hub Bendosari): Studi Kasus Jasa Pengiriman Cash On Delivery (COD) Shoope Express Hub Bendosari - Narwanto, Rohmad Dwi; Suryo, Herning; Sihabuddin, Sihabuddin (Solidaritas, 2024)
There is high interest in online shopping and there are many different types of payment methods to choose from, some with an advance transfer system, some via on-site payment or what we often interpret as COD or Cash On Delivery, COD or Cash on Delivery is a form of buying and selling transaction at the seller's place and buyers meet face to face at the same location whether they agree or not with what they promised during communication via short message or Whatsapp and so on. By using COD (Cash on Delivery) activities it will be easier and more practical, such as setting prices and the process for negotiating with buyers, in other words if there is money and goods, this is also done with good communication. This research aims to describe interpersonal communication between Shopee Express couriers hub Sukoharjo and shop customers during COD transactions. The methodology used byresearchers to collect data is qualitative and to determine informants using Purposive Random Sampling, namely by selecting informants by adding certain components to get the number of informants we expect. In this research, the theory of Harold D Lasswell was used and the result was that the courier's interpersonal communication with the customer did not cause misunderstandings regarding the delivery of the COD package so that it did not cause problems and could be profitable for both the courier and the customer who received the package.Keywords: Interpersonal Communication, Cash On Delivery, Courier, Customer